Recent Advances in g‑C3N4‑Based Donor–Acceptor Photocatalysts for Photocatalytic Hydrogen Evolution: An Exquisite Molecular Structure Engineering - Zhang, Qiang; Chen, Juan; Che, Huinan; Wang, Peifang; Liu, Bin; Ao, Yanhui (ACS materials letters, 2022)
Growing interest has been shown in photocatalytic hydrogen evolution (PHE) based on graphitic carbon nitride (g-C3N4, CN). The design of high-efficiency CN-based photocatalysts is a key to achieving high PHE performance. Herein, we offer a review to encapsulate the current approach in the thoughtful design of donor–acceptor type CN (DA-CN), which is an excellent tactic to optimize the photocatalytic properties of primal CN. Concretely, it starts with an introduction emphasizing the basic properties and limitations of primal CN as well as the superiority of DA-CN photocatalysts. Following that, the creation of DA-CN photocatalysts and the mechanism behind improved PHE performance are highlighted from three aspects, namely, interfacial heterojunction, molecular doping, and intramolecular D–A structure. Lastly, based on the previous work, a thorough overview on the primary difficulties and chances this hot area and the implications for future research are presented. Overall, it is envisioned that this review will provide a new perspective for revealing the application of DA-CN photocatalysts in PHE and adds invaluable knowledge for the development of more effective photocatalysts.